Einige Anmerkungen zur Entstehung von Grums Dogodek v mestu Gogi - Scherber, Peter (Slavistična revija, 2006)
The article focusses on three aspects of Slavko Grum's play Dogodek v mestu Gogi that have not received the ultimate explanation, i.e., the issue of stage conception, the issue when Grum began working on the drama, and the issue where the title and, particularly, the imaginary place Goga originate.
Keywords: Dogodek v mestu Gogi; ekspresionizem; expressionism; Grum, Slavko; Slovene drama; Slovene literature; slovenska dramatika; slovenska književnost